2018
DOI: 10.3847/1538-4357/aac3d7
|View full text |Cite
|
Sign up to set email alerts
|

Binarity and Accretion in AGB Stars: HST/STIS Observations of UV Flickering in Y Gem

Abstract: Binarity is believed to dramatically affect the history and geometry of mass loss in AGB and post-AGB stars, but observational evidence of binarity is sorely lacking. As part of a project to search for hot binary companions to cool AGB stars using the GALEX archive, we discovered a late-M star, Y Gem, to be a source of strong and variable UV and X-ray emission. Here we report UV spectroscopic observations of Y Gem obtained with the that show strong flickering in the UV continuum on time-scales of ≲ 20 s, chara… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…Multi-wavelength radio observations can distinguish between thermal and non-thermal emission (Sahai 2018a): since binarity is also expected to generate strong magnetic fields, ionized accretion-related flows can produce non-thermal, variable, emission, as we have found for Y Gem. The VLA lacks the sensitivity to make such observations except for a few ( < ∼ 5) of the brightest objects, but the ngVLA should be able to carry out a survey for a statistical sample of AGB stars (i.e., several 100) with UV emission with a modest time expenditure (∼ 1 hr per object to cover 4 bands in the 8-90 GHz range with a 5 σ sensitivity of about 3.5 μJy) (Sahai 2018a).…”
Section: Additional Probes Of Accretion Activitymentioning
confidence: 51%
“…Multi-wavelength radio observations can distinguish between thermal and non-thermal emission (Sahai 2018a): since binarity is also expected to generate strong magnetic fields, ionized accretion-related flows can produce non-thermal, variable, emission, as we have found for Y Gem. The VLA lacks the sensitivity to make such observations except for a few ( < ∼ 5) of the brightest objects, but the ngVLA should be able to carry out a survey for a statistical sample of AGB stars (i.e., several 100) with UV emission with a modest time expenditure (∼ 1 hr per object to cover 4 bands in the 8-90 GHz range with a 5 σ sensitivity of about 3.5 μJy) (Sahai 2018a).…”
Section: Additional Probes Of Accretion Activitymentioning
confidence: 51%
“…An even faster jet (630 km s −1 ) was found in the young PN MyCn 18 (Miszalski et al 2018). Binarity is believed to be responsible for jet formation, as recently observed in the symbiotic star R Aqr (Schmid et al 2017) and the AGB star Y Gem (Sahai et al 2018).…”
Section: Introductionmentioning
confidence: 75%
“…Yet there are numerous binary AGB stars without these features. More recently, AGB stars with UV excess and X-ray emission have been reported to exhibit flickering in the UV continuum on time-scales of a few seconds that would indicate accretion, possibly on a disc (Sahai et al 2018).…”
Section: Accretionmentioning
confidence: 99%
“…Asymptotic giant branch (AGB) stars show a variety of features in their ultraviolet (UV) spectra, and various mechanisms have been proposed to explain their characteristics. The IUE satellite (Sonneborn et al 1987) revealed a multitude of metallic emission lines, especially Fe II (Carpenter & Wing 1979) between 1200 and 3200 Å. AGB stars with intense far-UV emission and highexcitation emission lines have been suggested to be binaries (Sahai et al 2008(Sahai et al , 2018Ortiz & Guerrero 2016), whereas the correlation between the NUV GALEX magnitude and the visual light curve of Mira-type stars indicates that their near-UV emission follows the stellar pulsation and is thus 'intrinsic' to the star (Montez et al 2017).…”
Section: Introductionmentioning
confidence: 99%